2022
DOI: 10.1186/s12889-022-13489-y
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking and mental health outcomes among South Asian young adult survivors of sexual violence in the New York State Region

Abstract: Background Sexual violence is a growing issue faced across diverse South Asian American communities under the backdrop of a distinct religious and cultural environment that intersects with the ability to prevent and manage this public health crisis. There is also growing attention on sexual violence experienced by younger or second-generation South Asian Americans, although little is known on the prevalence of this violence and its impact on health outcomes. Using data from a community-driven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Middle-aged individuals are typically in better health ( 90 ) as they seek for medical help from themselves or others ( 91 ), follow medical advice ( 92 ), and receive progressive treatment ( 93 ). On the contrary, older adults may experience poorer treatment outcomes and a higher risk of death from depressive symptoms as aging may impair their perception ( 94 ), cognitive abilities ( 95 ), verbal expression ( 96 ), comprehension ( 97 ), help-seeking ability ( 98 ), and sabotage treatment collaboration and compliance ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Middle-aged individuals are typically in better health ( 90 ) as they seek for medical help from themselves or others ( 91 ), follow medical advice ( 92 ), and receive progressive treatment ( 93 ). On the contrary, older adults may experience poorer treatment outcomes and a higher risk of death from depressive symptoms as aging may impair their perception ( 94 ), cognitive abilities ( 95 ), verbal expression ( 96 ), comprehension ( 97 ), help-seeking ability ( 98 ), and sabotage treatment collaboration and compliance ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous women occupy the second place (23.7%) and female permanent (foreign) residents come next (18.6%). As in the case of male foreign offenders, where they appear to be disproportionately linked to the crime of rape, so foreign women (conversely) are found to be disproportionately represented as victims of rape; exhibiting, to an extent, intra-racial rape characteristics (Lim et al, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Another barrier to help-seeking for Latinx women was adherence to traditional gender norms. Similarly, South Asian survivors/victims attributed low help-seeking to religion, familial harmony, and other cultural factors ( Lim et al, 2022 ). Researchers have indicated that Black or African American women are significantly less likely than white women to disclose sexual assault to anyone ( McNair & Neville, 1996 ; Palmer & St. Vil, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%